Is the haematopoietic effect of testosterone mediated by erythropoietin? The results of a clinical trial in older men. (9th October 2012) - Maggio, M.; Snyder, P. J.; Ceda, G. P.; Milaneschi, Y.; Luci, M.; Cattabiani, C.; Masoni, S.; Vignali, A.; Volpi, R.; Lauretani, F.; Peachey, H.; Valenti, G.; et al.
Summary The stimulatory effects of testosterone on erythropoiesis are very well known, but the mechanisms underlying the erythropoietic action of testosterone are still poorly understood, although erythropoietin has long been considered a potential mediator. A total of 108 healthy men >65 years old with serum testosterone concentration <475 ng/dL were recruited by direct mailings to alumni of the University of Pennsylvania and Temple University, and randomized to receive a 60‐cm2 testosterone or placebo patch for 36 months. Ninety‐six subjects completed the trial. We used information and stored serum specimens from this trial to test the hypothesis that increasing testosterone increases haemoglobin by stimulating erythropoietin production. We used information of 67 men, 43 in the testosterone group and 24 in the placebo group who had banked specimens available for assays of testosterone, haemoglobin and erythropoietin at baseline and after 36 months. The original randomized clinical study was primarily designed to verify the effects of testosterone on bone mineral density. The primary outcome of this report was to investigate whether or not transdermal testosterone increases haemoglobin by increasing erythropoietin levels. The mean age ± SD of the 67 subjects at baseline was 71.8 ± 4.9 years. Testosterone replacement therapy for 36 months, as compared with placebo, induced a significant increase in haemoglobin (0.86 ± 0.31 g/dL, p = 0.01), but no change in erythropoietin levels (−0.24 ± 2.16 mIU/mL, p = 0.91). Included time‐varying measure of erythropoietin did not significantly account for the effect of testosterone on haemoglobin (Treatment‐by‐time: β = 0.93, SE = 0.33, p = 0.01). No serious adverse effect was observed. Transdermal testosterone treatment of older men for 36 months significantly increased haemoglobin, but not erythropoietin levels. The haematopoietic effect of testosterone does not appear to be mediated by stimulation of erythropoietin production.